Optimization of Areca catechu fronds as adsorbent for decolorization and COD removal of wastewater through the adsorption process - Muhd Nazmi Ismail; Hamidi Abdul Aziz; Mohd Azmier Ahmad; Nik Athirah Yusoff (Universiti Kebangsaan Malaysia, 2015)
Areca catechu fronds show higher capability for removal of color and COD and were utilized as an adsorbent for adsorption process. Areca catechu fronds activated carbon (AC) undergoes activation process after carbonization under purified carbon dioxide and turned as activated carbon. Three variables were chosen for the preparation optimization which consists of temperature, activation time and impregnation ratio in order to study the effect toward the removal of color and COD from cotton textile mill wastewater. For this study, the response surface methodology (RSM) was employed. Quadratic model were develop based on three variables and responses of color and COD. High values of the coefficient determination, R2 were obtained from analysis of variance (ANOVA) for both responses. The optimum Areca catechu fronds activated carbon (AC) preparation condition was established at temperature 797 °C for 1.57 hour of activation time and 2.75 impregnation ratios, corresponding to the removal of color and COD with 78.83 and 62.41%, respectively.